2018
DOI: 10.1016/j.jmii.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein levels can predict positive 18F-FDG PET/CT findings that lead to management changes in patients with bacteremia

Abstract: A majority (54.1%, n = 40) of the patients with positive F-FDG PET/CT results underwent treatment modifications; they accounted for most cases (87%) of management changes in our cohort. Leukocytosis and increased CRP levels are significantly associated with positiveF-FDG PET/CT findings in patients with bacteremia. CRP levels >54.025 mg/L were accurate predictors of positive F-FDG PET/CT results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In addition, three patients had elevated Creactive protein within 5 days of the PET/CT investigation. In one previous study of patients with bacteremia by Tsai et al, it was reported that the C-reactive protein level was positively correlated with SUVavg of the spleen [24]. Thus, in the present study, elevated C-reactive protein may have produced the increase in [ 18 F] FDG uptake in the spleen observed in three patients.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, three patients had elevated Creactive protein within 5 days of the PET/CT investigation. In one previous study of patients with bacteremia by Tsai et al, it was reported that the C-reactive protein level was positively correlated with SUVavg of the spleen [24]. Thus, in the present study, elevated C-reactive protein may have produced the increase in [ 18 F] FDG uptake in the spleen observed in three patients.…”
Section: Discussionsupporting
confidence: 66%
“…Berrevoets et al [59] and Tsai et al [60] only assessed treatment and found FDG-PET/CT to facilitate changes in 74% and 54.1%, respectively, whereas the fraction of treatment changes only constituted 14.7% of the high impact cases in the aforementioned study by Brøndserud et al [61]. Another approach to personalized treatment based on FDG-PET/CT was presented in another study by the group of Berrevoets et al, i.e.…”
Section: Bacteremiamentioning
confidence: 99%
“…For instance, some studies describe the number of metastatic foci whilst others present a detection rate for infectious foci, which is in essence just semantics thus, despite different designation studies find comparable rates for the detection of infectious/metastatic foci, i.e. 45.8-73.7% [56,57,[59][60][61][62][63]. It is noteworthy that Berrevoets et al found 71.2% of the patients with metastatic foci (73.7% of all patients) to be without any signs or symptoms to suggest localization of such foci [59], and Brøndserud et al [61] corroborated the finding that FDG-PET/CT is the incremental modality in a significant proportion, i.e.…”
Section: Bacteremiamentioning
confidence: 99%
“…Bacteriemia of unknown origin is a further condition linked to FUO, in which 18 F-FDG PET may help the identification of the infectious focus, particularly in pediatric [38,39] or immunocompromised patients with acquired immune deficiency syndrome (AIDS) [40].…”
Section: Fever Of Unknown Origin (Fuo)mentioning
confidence: 99%